Seyfert galaxies and "Unified Scheme" - Pahshchenko, I.N.; Pilipenko, S.V.; Vitrishchak, V.M. (Advances in Astronomy and Space Physics, 2011)
From spectroscopic point of view Seyfert galaxies (as other Active Galactic Nuclei - AGN) basically are subdivided into two types: with and without broad permitted emission lines in their optical spectra (so called type I and type II Seyfert galaxies or AGNs). One of the most fundumental idea concerning AGN is that observed AGN type (I or II) is determined by inclination angle of AGN to the line of sight (LOS). At high inclination angles LOS crosses dusty torus which absorbs and scatters line emission. But in some recent papers the differences in close (< 100 kpc) environment of SyI and SyII (SyII have more close
companions), which are incompatible with Unification Scheme, were found and the possibility of physical (intrinsic) differences between Seyfert I and II was discussed. It was shown that this difference could be due to selection effects caused by the sample criteria. We sampled SyI and SyII galaxies from the Sloan Digital Sky Survey (SDSS) on the basis of their emission line properties thus excluding selection and discuss the properties of the environment of Seyfert galaxies.